1970
DOI: 10.1029/rs005i001p00019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of Magnetic Field Effects on VLF Propagation at Night

Abstract: Computations of nighttime field intensity versus distance are made for a 23.4‐kHz signal radiated from Hawaii and for propagation paths to Seattle, Ontario (California), Samoa, and Wake Island. The computations were made by using the waveguide computer program developed at the Naval Electronics Laboratory Center to obtain waveguide mode constants, each 2° of arc or 222 km along each path. An exponential electron‐density profile defined by β = 0.5 km−1 and h′ = 85.5 was assumed, where β and h′ are defined by Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 6 publications
7
35
0
Order By: Relevance
“…Airborne amplitude recordings, conducted continuously along flights over portions of the propagation baselines, observed that there was more attenuation on the east-to-west than on the west-to-east path (see Figs. 7-8 and discussion thereof, in Bickel et al, 1970). On the other hand, the amplitudes on the east-to-west path were highly variable from day to day.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Airborne amplitude recordings, conducted continuously along flights over portions of the propagation baselines, observed that there was more attenuation on the east-to-west than on the west-to-east path (see Figs. 7-8 and discussion thereof, in Bickel et al, 1970). On the other hand, the amplitudes on the east-to-west path were highly variable from day to day.…”
Section: Discussionmentioning
confidence: 97%
“…Two of these reports are from the United States Naval Electronics Laboratory Center or NELC (subsequently named Naval Ocean Systems Center or NOSC) and deal with the same dataset, gathered in 1969. The earlier of these reports (Bickel et al, 1970) compared signal-propagation paths from Hawaii roughly east-to-west to Wake Island, and from Hawaii roughly west-to-east to southern California. The signal was the 23.4-kHz transmission from the NPM beacon in Hawaii.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an MF radar requires a large facility. Standard radio wave signals propagated from VLF and low frequency (LF) transmitters have also been used to measure the height variation of the D region, based on phase and intensity modulations [e.g., Bickel et al, 1970;Thomas and Harrison, 1970;Thomson et al, 2007], but the possible region for electron density measurements is limited along the propagation path between the transmitter and the receiver.…”
Section: Introductionmentioning
confidence: 99%
“…The program used for the mode parameter calculations reported here is a slightly modified version of the NOSC program MODEFNDR which is very similar to MODESRCH. Further discussion of the very complex mathematical details of the NOSC VLF propagation program and comparisons with experimental data can be found in Bickel et al (1970) and Pappert and Hitney (1988). The output of MODEFNDR then comprises the excitation factors, height gain functions, attenuation factors and horizontal wave numbers for allowable VLF modes.…”
Section: Details Of the Computation Of Vlf Propagation Perturbationsmentioning
confidence: 99%